Program Corporate Social Responsibility PT SHARP Electronics Indonesia melalui Pemberdayaan Masyarakat “Kebun Gizi” di Desa Sirnabaya Teluk Jamber Kabupaten Karawang Jawa Barat - Siti Qona’ah (Jurnal Komunikasi, 2017)
Empowering people with the theme of "Kebun Gizi" is a program of corporate social responsibility conducted by  PT. SHARP Electronics Indonesia in 2016. Corporate Social Responsibility program which consists of planting crops in hydroponic systems. This study was to determine the program of Corporate Social Responsibility PT SHARP Electronics Indonesia through Community Empowerment. In this study, researchers used a qualitative approach and case studies, as a method of research which illustrates that "Kebun Gizi”  is a part of corporate social responsibility activities in the field of community development in Dusun Pejaten RT 04/02, Desa Sirnabaya Teluk Jamber Karawang, West Java. Thus with corporate social responsibility through community empowerment can improve people's lives Keywords: Corporate Social Responsibility, Community Empowerment, Kebun Gizi